Formulate a Waste Bank Management Model in Pekanbaru City by Recycling The Material for Environmental Hygiene - ., Elmawati; ., Zulkarnain; ., Suwondo; Karnila, Rahman (Journal of Ecohumanism, 2024)
Background and objectives: With various policies and systems at each waste bank, the effectiveness of waste banks in attracting people to manage their waste has not been running well, so they have not been able to provide solutions to the waste problem in Pekanbaru City and have not been integrated. This research aims to formulate a waste bank management model in Pekanbaru City. Method: This research uses quantitative and qualitative research methods with a descriptive approach. This research was conducted using questionnaires, interviews, and observations. Interviews were conducted using Google form with the Director of the Main Waste Bank (BSI), Chair of the Waste Bank Unit (BSU), Business Actors, NGOs, Academics, Head of the Sumatra Ecoregion Development Control Center (P3ES), Environmental and Hygiene Service Officials, Subdistrict Heads and Village Heads. Results: The characteristics of the waste bank in Pekanbaru City regarding planning are inadequate. In terms of organization, it is well structured, but most of the members have multiple jobs. In terms of direction, it has been implemented, but not evenly. In terms of control, it is still manual and has not utilized technology. The dominant factor in waste bank management in Pekanbaru City is economic factors, with a p-value <0.001. Conclusion: The waste bank management model in Pekanbaru City is to control the higher prices given to BSU and customers, so BSI must carry out integrated processing of segregated waste that has been collected at BSI by recycling the material.